Differential uptake mechanisms of fluorescent substrates into stem-cell-derived serotonergic neurons - Matthäus, Friederike; Schloss, Patrick; Lau, Thorsten (ACS chemical neuroscience, 2015)
The actions of the neurotransmitters serotonin, dopamine, and norepinephrine are partly terminated by diffusion and in part by their uptake into neurons via the selective, high-affinity transporters for serotonin (SERT), dopamine (DAT), and norepinephrine (NET), respectively. There is also growing evidence that all three monoamines are taken up into neurons by low-affinity, high-capacity organic cation transporters (OCT) and the plasma membrane monoamine transporter (PMAT). Pharmacological characterization of these low-affinity recombinant transporter proteins in heterologous expression systems has revealed that they are not antagonized by classical inhibitors of SERT, DAT, or NET but that decynium-22 (D22) antagonizes OCT3 and PMAT, whereas corticosterone and progesterone selectively inhibit OCT3. Here, we show that SERT, PMAT, and OCT3, but not OCT1 and OCT2, are coexpressed in murine stem cell-derived serotonergic neurons. Using selective antagonists, we provide evidence that uptake of the fluorescent substrates FFN511, ASP+, and 5-HT into stem cell-derived serotonergic neurons is mediated differentially by these transporters and also involves an as yet unknown transport mechanism.